Activation of pial and dural macrophages and dendritic cells by cortical spreading depression. Issue 3 (13th March 2018) - Schain, Aaron J.; Melo‐Carrillo, Agustin; Borsook, David; Grutzendler, Jaime; Strassman, Andrew M.; Burstein, Rami
Abstract : Objective: Cortical spreading depression (CSD) has long been implicated in migraine attacks with aura. The process by which CSD, a cortical event that occurs within the blood–brain barrier (BBB), results in nociceptor activation outside the BBB is likely mediated by multiple molecules and cells. The objective of this study was to determine whether CSD activates immune cells inside the BBB (pia), outside the BBB (dura), or in both, and if so, when. Methods: Investigating cellular events in the meninges shortly after CSD, we used in vivo two‐photon imaging to identify changes in macrophages and dendritic cells (DCs) that reside in the pia, arachnoid, and dura and their anatomical relationship to TRPV1 axons. Results: We found that activated meningeal macrophages retract their processes and become circular, and that activated meningeal DCs stop migrating. We found that CSD activates pial macrophages instantaneously, pial, subarachnoid, and dural DCs 6‐12 minutes later, and dural macrophages 20 minutes later. Dural macrophages and DCs can appear in close proximity to TRPV1‐positive axons. Interpretation: The findings suggest that activation of pial macrophages may be more relevant to cases where aura and migraine begin simultaneously, that activation of dural macrophages may be more relevant to cases where headache begins 20 to 30 minutes after aura, and that activation of dural macrophages may be mediated by activation of migratory DCs in the subarachnoid space and dura. The anatomical relationship between TRPV1‐positive meningeal nociceptors, and dural macrophages and DCs supports a role for these immune cells in the modulation of head pain. Ann Neurol 2018;83:508–521